EEG alpha activity during imagining creative moves in soccer decision-making situations. (June 2018) - Fink, Andreas; Rominger, Christian; Benedek, Mathias; Perchtold, Corinna M.; Papousek, Ilona; Weiss, Elisabeth M.; Seidel, Anna; Memmert, Daniel
Abstract: This study investigated task-related changes of EEG alpha power while participants were imagining creative moves in soccer decision-making situations. After presenting brief video clips of a soccer scene, participants had to imagine themselves as the acting player and to think either of a creative/original or an obvious/conventional move (control condition) that might lead to a goal. Performance of the soccer task generally elicited comparatively strong alpha power decreases at parietal and occipital sites, indicating high visuospatial processing demands. This power decrease was less pronounced in the creative vs. control condition, reflecting a more internally oriented state of information processing characterized by more imaginative mental simulation rather than stimulus-driven bottom-up processing. In addition, more creative task performance in the soccer task was associated with stronger alpha desynchronization at left cortical sites, most prominently over motor related areas. This finding suggests that individuals who generated more creative moves were more intensively engaged in processes related to movement imagery. Unlike the domain-specific creativity measure, individual's trait creative potential, as assessed by a psychometric creativity test, was globally positively associated with alpha power at all cortical sites. In investigating creative processes implicated in complex creative behavior involving more ecologically valid demands, this study showed that thinking creatively in soccer decision-making situations recruits specific brain networks supporting processes related to visuospatial attention and movement imagery, while the relative increase in alpha power in more creative conditions and in individuals with higher creative potential might reflect a pattern relevant across different creativity domains. Highlights: Participants imagined creative moves in soccer decision-making situations. Soccer task performance was associated with motor imagery and visuospatial demands. Individual differences in creativity modulated brain activity during task performance.